Identifikasi dan Karakterisasi Isolat Rhizobacteri Osmotoleran dari Merapi - Agung Astuti (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2016)
Rhizobacteri Merapi isolates have been detected, and MA, MB, and MD isolates could withstand osmotic stress up to 2.75 M NaCl. MD isolate was stronger in dissolving phospate than MA and MB isolates, but MA and MB isolates had much stronger nitrification capability and could perform ammonification than MD isolate. This research studied about Rhizobacteri Merapi isolates as identification, as well as their characterization. The results show that there is a difference in colonial characteristic of four Rhizobacteri Merapi isolates where MB and MC isolates (white circular-entire shape), except for MA isolate (curled-white with undulate edge) and MC isolate (ramose-yellow with filamentous edge) and also that MD isolate have the largest diameter (1,5 mm). Cell characteristics, however, were the same, gram-negative and were rod shaped, except for MD isolate (coccus). All showed aerob and fermentative characteristics, although MD isolate was able to very strongly hydrolyze starchs. The growth type is fast growing which reach log phase for after 48 hours and then the number of colony decrease.